Ecology and Migrations of the Green Macaw - Chassot, Olivier (2004)
The Great Green Macaw (Ara ambigua) is a spe-cies which performs seasonal altitudinal migra-tions between it’s nesting range in the northern lowlands of the Caribbean slopes of Costa Rica and it’s post-breeding range, especially on the northern slopes of the Central Volcanic Range. Based on the data of these movements obtained through a long range study involving telemetry techniques, conservation initiatives are being im-plemented, taking into account the value of the breeding and post-breeding range of the species with  the  aim  to  preserve  a  unique  sample  of ecosystems barely represented in the system of wildlife protected areas of Costa Rica.